ANALYSIS OF FIGURATIVE LANGUAGE IN THE SPEECH OF PRESIDENT JOKOWI IN G20 SUMMIT 2022 - Imelda Oppusunggu; Tiarma Intan Marpaung; David Togi Hutahaean (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research is concerned in analyzing of figurative language in the speech of President Jokowi in G20 Summit 2022 in the opening part of the speech. In this research, problems arise regarded the types and meaning of figurative language and the most dominant type of figurative language in the speech of President Jokowi in G20 Summit 2022. This research used the figurative language based in Perrine’s theory perception (1977:61). Figurative language consist of 12 kinds, there are; simile, metaphor, personification, apostrophe, synecdoche, metonymy, symbol, allegory, paradox, hyperbole/overstatement, understatement and irony. The methodology used in this research is qualitative research and this research used the content method. Document or content analysis is a research method applied to written or visual material with the aim of identifying certain characteristics of that material. The data in this research is speech of President Jokowi in G20 Summit 2022. After investigated the types of figurative language in the speech of President Jokowi in G20 Summit 2022, researcher found total of 15 sentences contained figurative language in the speech of President Jokowi. There are 5 types of figurative language used in the speech of President Jokowi from the 12 types of figurative language proposed by Perrine (1977:61). There are five types of figurative language found in President Jokowi's speech, namely: synecdoche: 5 data, metonymy: 3 data, paradox: 3 data, metaphor: 2 data, and irony: 2 data. The most dominant types of figurative language in the speech of President Jokowi in G20 Summit 2022 are synecdoche which represents were synecdoche 34%, metonymy 20%, paradox 20%, metaphor 13%, irony 13%. It can be concluded that President Jokowi's speech contains wise sentences and explains the essence of what he wants to convey to the audience, so that the audience is interested in listening and understanding the contents of the speech.